Glucose transporter 1 in rheumatoid arthritis and autoimmunity. (21st February 2020) - Zezina, Ekaterina; Sercan‐Alp, Oezen; Herrmann, Matthias; Biesemann, Nadine
Abstract: Knowledge about metabolism of immune cells increased almost exponentially during the last two decades and thereby created the new area immunometabolism. Increased glucose uptake and glycolysis were identified as one of the major drivers in immune cells for rapid adaptation to changes in the microenvironment or external stimuli. These metabolic switches are crucial to generate macromolecules for immune cell proliferation and activation. Glucose transporter 1 (GLUT1), a ubiquitously expressed glucose transporter, is strongly upregulated after innate and adaptive immune cell activation. Deletion or inhibition of GLUT1 blocked T cell proliferation and effector function, antibody production from B cells and reduced inflammatory responses in macrophages. Increased glucose uptake and GLUT1 expression are not only observed in proinflammatory conditions, but also in murine models of autoimmunity as well as in human patients. Rheumatoid arthritis (RA), the most common autoimmune disease, is characterized by infiltration of immune cells, hyperproliferation of fibroblast‐like synoviocytes, and destruction of cartilage and bone. These processes create a hypoxic microenvironment in the synovium. Moreover, synovial samples including fibroblast‐like synoviocytes from RA patients showed increased lactate level and upregulate GLUT1. Similar upregulation of GLUT1 is observed in systemic lupus erythematosus and psoriasis patients as well as in murine autoimmune models. Inhibition of GLUT1 using either T cell specific knockouts or small molecule GLUT1/glycolysis inhibitors improved phenotypes of different murine autoimmune disease models like arthritis, lupus, and psoriasis. Thereby the therapeutic potential of immunometabolism and especially interference with glycolysis was proven. This article is categorized under: Biological Mechanisms > Metabolism Translational, Genomic, and Systems Medicine > Translational Medicine Physiology > Mammalian Physiology in Health and Disease Abstract : Increased glucose uptake via the glucose transporter 1 (GLUT1) is essential for immune cell activation and is upregulated in different autoimmune diseases, like rheumatoid arthritis. Interference with GLUT1 using either genetic deletion or small molecules seems promising in different autoimmune mouse models and highlights the therapeutic potential of immunometabolism.